Perbedaan daya hambat terhadap Streptococcus mutans dari beberapa pasta gigi yang mengandung herbal (The difference of inhibition zones toward Streptococcus mutans among several herbal toothpaste) - Rini Pratiwi (Dental Journal (Majalah Kedokteran Gigi), 2005)
Prevention of dental caries and periodontal disease with health promotion has been the main goal of Dentistry, since the dental plaque is a common and predominating factor leading to loss of teeth both caused by both dental caries and periodontal disease. Most devices used for plaque removal and periodontal care are based on mechanical action, including toothbrushes, interdentally brushes and oral irrigators. Today, plaque control is facilitated by an increasing variety of active agents based on either natural ingredients or synthetic product. Alternative materials based on essential oil and plant extracts are therefore of particular interest. The aim of the present study was to investigate the different of zone inhibition of Streptococcus mutans of herbal toothpastes. Samples of the subjects were 4 types of herbal toothpastes and 1 herbal toothpaste as control. For inhibition zone trial toward Streptococcus mutans, agar diffusion method was used and the interpretation was done by measuring the widest inhibition zone. The result of the study indicated a statistical significance different on inhibition zone among the 5th toothpastes, but toothpaste containing siwak was the widest inhibition zone.